Comparative Analysis of The Content of Developing Ethnopedagogical Competence In Future Teachers on The Basis of International Experiences - Saidovna, Turdiyeva (Intelektualitas Jurnal Penelitian Lintas Keilmuan, 2025)
This article analyzes the role of innovative technologies in the development of acmeological abilities of school music teachers. The study used questionnaires, tests and observation methods, and studied the activities of 60 music teachers. The results showed that innovative technologies are an effective tool for increasing the professional growth and creative potential of teachers. It also identified the need for further development of technical support and methodological knowledge. The article concludes with recommendations and practical suggestions.